2012
DOI: 10.1176/appi.ps.201100233
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Antidepressant Use Among Older Home Health Care Patients

Abstract: Objective The objective of this study is to determine the effect of race (black versus white) on depression diagnosis and antidepressant use in older Home Healthcare patients. Methods Cross-sectional data were obtained from the 2007 National Home and Hospice Care Survey of patients 65+ years (N=3,157). Participants were analyzed by race, antidepressant use, and charted depression diagnosis. Results In whites compared to blacks, there were greater odds of receiving a depression diagnosis (OR=4.06, 95% CI=1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
1
10
1
Order By: Relevance
“…Specifically, this study showed an increased likelihood of antidepressant medications prescribed to older Caucasian patients rather than older minorities regardless of depression screen results. African Americans repeatedly had the lowest odds of receiving an antidepressant prescription, compared to the other racial/ethnic groups, a finding also reported in previous work from our group on racial disparities in depression treatment within HH 3 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Specifically, this study showed an increased likelihood of antidepressant medications prescribed to older Caucasian patients rather than older minorities regardless of depression screen results. African Americans repeatedly had the lowest odds of receiving an antidepressant prescription, compared to the other racial/ethnic groups, a finding also reported in previous work from our group on racial disparities in depression treatment within HH 3 .…”
Section: Resultssupporting
confidence: 86%
“…These changes began January 2010, resulting in most agencies incorporating the Patient Health Questionnaire (PHQ)-2, a depression screening measure widely used in primary care 2 , into their routine nursing assessment. Results of national survey data have shown lower antidepressant prescription rates in older minorities, specifically African American home healthcare patients, compared to Caucasians 3 , but these data were collected prior to changes in Medicare regulations. Therefore, any change in depression treatment based on the effects of widespread use of the PHQ-2 in home healthcare have not yet been reported.…”
Section: Objectivementioning
confidence: 99%
“…Older African Americans nursing home residents were less likely to receive an antidepressant and/or psychotherapy than Caucasians (Adjusted Odds Ratios (AOR) = 0.79, p<0.05) (Siegel et al, 2012). Older Caucasians within home healthcare had greater odds of receiving an antidepressant medication than older African Americans (AOR=2.75; 95% CI=1.67–4.57) (Pickett et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…In a recent national sample of US elderly patients receiving home healthcare, Caucasians were significantly more likely than African-Americans to have a formal depression diagnosis noted in their home healthcare chart (OR=4.06, 95% CI=1.66–9.93). [24] Future research is needed to determine whether this finding reflects differences in depression recognition, documentation, or transfer of clinical information across health care settings.…”
Section: Prevalence and Correlates Of Depression In Home Healthcarementioning
confidence: 99%
“…[18] Moreover, over 40% of these treated patients received inadequate treatment due to under-dosing compared to evidence-based guidelines or to patient non-adherence. While rates of identification and treatment of depression in home healthcare patients have risen sharply in the past decade,[24, 35, 36] most patients with clinically significant depressive symptoms are still either not being treated or are being treated inadequately. Reasons for inadequate treatment range from patients’ refusal or nonadherence to physicians’ not following evidence-based guidelines in prescribing or in adjusting treatment in response to persistent symptoms.…”
Section: Treatmentmentioning
confidence: 99%